Democracy without justice in Spain : the politics of forgetting - Encarnación, Omar Guillermo, 1962- (Pennsylvania studies in human rights., 2014)
Rather than seek retribution and reconciliation, Spain's political leaders agreed to place the Civil War and the Franco dictatorship in the past. Omar G. Encarnación examines the political factors that made possible the "politics of forgetting" and explores the advantages and consequences of democratizing without confronting the past.